Jaffa Shared and Shattered : Contrived Coexistence in Israel/Palestine - Monterescu, Daniel (Book collections on Project MUSE., 2015)
"Multiethnic cities--where the political "other" is also a neighbor--play a pivotal role in situations of long-term conflict, and few places have been more marked by the tension between intimate proximity and visceral hostility than Jaffa, one of the "mixed towns" of Israel/Palestine. Daniel Monterescu argues that such places challenge our assumptions about national identity and challenge the Israeli state's goal of maintaining homogeneous, segregated, and ethnically stable spaces. In this nuanced ethnographic and historical study, he analyzes everyday interactions, life histories, and uses of space, describing the politics of gentrification and the circumstantial coalitions that define the city. Drawing on key theorists in anthropology, sociology, urban studies, and political science he outlines a relational theory of sociality and spatiality"--